Temperature-dependent residual stress in aerosol-deposited barium titanate films - Kuhfuß, Michel; Eckstein, Udo; Urushihara, Daisuke; Asaka, Toru; Xie, Lixu; Martin, Alexander; Kakimoto, Ken ichi; Webber, Kyle Grant (Ceramics International, 2025)
Aerosol deposition is a promising technique for preparing thick, dense ceramic films on various substrates at room temperature. However, the resulting microstructure shows disadvantages for certain applications; for instance, defects and residual stresses are, together with the nanocrystalline grains, responsible for the low functional properties of aerosol-deposited films, limiting their usability for applications such as piezoelectric energy harvesting. As such, this study investigates the relaxation of aerosol deposition-induced defects and residual compressive stress during annealing. Barium titanate films with a 10–15 μm thickness are sprayed on stainless steel substrates as a model material system. While as-deposited films display linear dielectric behavior, ferroelectricity can partially be recovered by annealing up to 600 °C. This is proposed to be connected with a reduction in compressive residual stress that is directly observed using in situ temperature-dependent X-ray diffraction. Above 250 °C, a transition from compressive towards tensile stress can be found, which is caused by thermal expansion and an observed shrinkage of the film. This shrinkage is proposed to be connected to a recombination of defects, e.g., oxygen vacancies. After annealing up to 700 °C, the residual stress is permanently reduced from −420 MPa to −320 MPa, and defects, such as the non-crystalline grain boundary areas observed in transmission electron microscopy, are partially relaxed. However, annealing temperatures above 500 °C could be responsible for reintroducing additional compressive stress due to the thermal expansion mismatch between film and substrate.
CRIS-Team Scopus Importer:2025-10-24
Keywords: BaTiO; Dielectric properties (C); Films (A); X-ray methods (B)